(untitled) (CIPEEX, 2022)
ABSTRACT: IT WAS UNDERSTOOD THAT THE CRITERIA OF AVAILABLE SUITORS REGISTERED IN THE NATIONALADOPTION AND FOSTERING SYSTEM (SNA) IN BRAZIL HAS A WELL DEFINED AND FAIR STANDARD. CURRENTLY,STILL ACCORDING TO THE SNA (2021), THERE ARE 32.831 CANDIDATES FOR ADOPTION IN BRAZIL AND 4.263AVAILABLE CHILDREN. SO, IF THERE ARE ALMOST 8 APPLICANTS FOR EVERY 1 CHILD, WHY HAVEN’T THEY ALLBEEN ADOPTED YET? LET’S ANALYZE THE CRITERIA ADOPTED FOR THE CHOICE OF THE APPLICANTS REGISTERED IN THE SNA AND THE REASONS FOR THE NON-ADOPTION. TO ACHIEVE THE EXPECTED RESULTS, THE FOLLOWING SPECIFIC OBJECTIVES WERE DEFINED: A) DEFINE THE STANDARDS IMPOSED BY THE APPLICANTS, B) ANALYZE THE PROFILES OF THE AVAILABLE CHILDREN, C) DISCUSS THE NUMERICAL IMBALANCE BETWEEN APPLICANTS AND AVAILABLE CHILDREN. STILL ACCORDING TO THE SNA, AMONG THE 32,831 APPLICANTS FOR ADOPTION, ONLY 4 WANT TO ADOPT TEENAGERS UP TO OR OVER 15 YEARS OLD, WHILE OF THE 4,263 AVAILABLE CHILDREN MORE THAN 1,000 ARE UP TO OR OVER 15 YEARS OLD. (HAS THIS PATTERN). THE WAY OUT WOULD BE NOT TO LET THE APPLICANTS CHOOSE ONE STANDARD CHILD TO ADOPT, BUT TO LET THE CHILDREN CHOOSE WHICH FAMILY TO STAY WITH, AND THE APPLICANTS WHO HAVE DECIDED TO ADOPT ARE ALREADY AWARE THAT THEY HAVE NOT CHOSEN THE CHILD, NOR HIS OR HER AGE OR COLOR. AFTER THE CHILDREN REACH THE AGE OF MAJORITY, THEY ARE LEFT DESTITUTE AND GO TO FOSTER HOMES, WITHOUT ACCESS TO EDUCATION AND JOBS. ON THE OTHER HAND, THE LAW PROJECT N° 2528, OF 2020, WAS APPROVED. ONE OF THE INITIATIVES FORESEEN IN THE TEXT IS THAT SHELTERS AND HOST INSTITUTIONS ADOPT AS A PRINCIPLE THE GRADUAL PREPARATION OF ORPHANED ADOLESCENTS FOR DISENGAGEMENT, WITH VOCATIONAL AND TECHNICAL HIGH SCHOOL EDUCATION. THESE HOMES MUST ENSURE THAT ADOLESCENTS AGED 14 TO 18 ARE PREPARED FOR AND HAVE ACCESS TO THE LABOR MARKET.